Semidirect restorations in multidisciplinary treatment: viable option for children and teenagerssemidirect restorations in multidisciplinary treatment: viable option for children and teenagers - Tonetto, Mateus Rodrigues; Frizzera, Fausto [UNESP]; Silva, Monica Barros da; Bhandi, Shilpa H.; Kuga, Milton Carlos [UNESP]; Pereira, Kamila Figueiredo [UNESP]; Pinzan-Vercelino, Celia Regina Maio; Bandéca, Matheus Coelho (Jaypee Brothers Medical Publishing, 2015)
Due to the esthetic necessity required nowadays, the multidisciplinar treatment became a fundamental step in the restoration success. When the patient exhibits dental agenesis of one or more elements, he can show difficulty in social interactions. The age of the patient is a limiting factor to esthetic procedures, however, it should be evaluated as a real indicative with each case. The utilization of semi-direct restorations is a viable option due the cost, esthetic and improvement of physical and mechanical properties. The purpose of this paper is to present a case detailing the confection and cementation of anterior semi-direct restorations aimed at an anatomic reestablishment associated with integrated treatment with periodontics and orthodontics.
Keywords: Indirect-direct restoration; Multidisciplinary approach; Dental agenesis; Esthetic dentistry; Dental esthetics; Permanent dental restoration